What's social about social cognition? : research on socially shared cognition in small groups - Nye, Judith L.; Brower, Aaron M. (SAGE Publications, 1996)
Cognition research has become a major area within psychology - particularly social psychology. However, social cognitive research tends to focus on the individual, neglecting the impact of social interaction on the individual's cognitive processes, while group process research tends to neglect the cognitive processes of individual group members and their influence on the group. This volume fills these gaps in the literature and brings the two research areas together: contributions from key scholars in both fields offer empirical research that moves beyond the traditional boundaries of social research.